Colonial institutions and long-run economic performance in Colombia: is there evidence of persistence? (2005)
A recent body of literature has claimed that differences in long-run economic performance within the Americas stem from the different institutional structures established during colonial times. This research tries to find evidence of institutional persistence in Colombia using direct measures of colonial institutions, particularly the intensity of encomiendas, slavery and State presence. The paper deals with the possible endogeneity of colonial institutions developing an instrumental variables strategy based upon colonial institutional design. We find evidence of institutional persistence of encomienda, slavery and State capacity on a series of current socioeconomic outcomes.